THE ANALYSIS OF CHINESE SERVICE QUALITY OF THAI TOUR GUIDES : A CASE STUDY OF THE EVALUATION OF CHINESE TOURISTS - KANCHANADUSADE, SIRIDHON; NING ZHU, GONG; PING, ZHAO (Chinese Language and Culture Journal, 2016)
This research studied the use of Chinese language of Thai tour guides by interviewing the management of Saeng Thai Trade & Travel Co.,Ltd. as well as surveying the Chinese speaking tourists under this company in the area of Bangkok and Pattaya, Chonburi. The research focused on the evaluation of service quality of Thai guides during their Chinese practitioning such as welcoming, introducing and providing knowledges, for instance, tourist activities, accommodations, dining, shopping and etc. The study shows a great level of satisfaction in service and a fair impression on the presentation of knowledge of tourist attractions and of Thai culture. This research reflecting that the abilities of Thai tour guides still need improvement in order to give the best information to tourists. It clearly shows that this research should be supported and encouraged to the government and other related facilities to including proposing to declare a policy which will give The Business Chinese Test (BCT) to increase efficiency and quality of guides; therefore, it will substantially increase the number of tourists in Thailand, thus, more benefit for our country